2015
DOI: 10.1371/journal.pone.0123480
|View full text |Cite
|
Sign up to set email alerts
|

Human Electroretinal Responses to Grating Patterns and Defocus Changes by Global Flash Multifocal Electroretinogram

Abstract: The electrical response of the retina was examined as a function of retinal region, using stimuli of various spatial frequencies in the first experiment. In the second experiment, the regional response of the retina to defocus at high and low spatial frequencies was investigated. Twenty three subjects were recruited for global flash multifocal electroretinogram (mfERG) in experiment 1. Black and white gratings (printed on plastic transparent sheets) of four spatial frequencies (SF), 0.24, 1.2, 2.4 and 4.8 cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 76 publications
(100 reference statements)
4
42
1
Order By: Relevance
“…Previous studies of the effects of optical defocus on mfERG responses from human retina have shown that gmfERG response amplitudes tend to increase with imposed myopic defocus and decrease with hyperopic defocus, with the effects most pronounced in the mid-peripheral retina. [14][15][16] These previous findings appear to be at odds with the results of the present study in which areas of the retina experiencing more naturally occurring myopic defocus tended to exhibit lower response amplitudes than areas experiencing hyperopic defocus. There are several potential reasons for this apparent discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Previous studies of the effects of optical defocus on mfERG responses from human retina have shown that gmfERG response amplitudes tend to increase with imposed myopic defocus and decrease with hyperopic defocus, with the effects most pronounced in the mid-peripheral retina. [14][15][16] These previous findings appear to be at odds with the results of the present study in which areas of the retina experiencing more naturally occurring myopic defocus tended to exhibit lower response amplitudes than areas experiencing hyperopic defocus. There are several potential reasons for this apparent discrepancy.…”
Section: Discussioncontrasting
confidence: 99%
“…The DC component of the gmfERG represents a pooled response predominantly derived from photoreceptor and bipolar cell activity, whereas the IC component is thought to derive from cells within the inner retina (ganglion and amacrine cells) . Previous gmfERG experiments have reported a sign‐dependent response to imposed retinal defocus, with higher gmfERG amplitudes occurring with plus lens wear (focal plane located anterior to the retina, creating myopic retinal defocus) and reduced amplitudes with minus lens wear (creating hyperopic defocus) . However, although these experiments attempted to differentiate the response to imposed defocus at different retinal eccentricities, they did not directly quantify the sign or magnitude of defocus at these peripheral regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Previous research in humans has shown that gmfERG responses are altered under conditions of retinal defocus, increasing with myopic defocus and decreasing with hyperopic defocus, with the effects most pronounced in the midperipheral retina. 21,22 The aim of this study was to investigate the effect of atropine on neural activity in the human retina under shortterm imposed defocus. We hypothesized that if the antimyopia effects of atropine are based on a retinal site of action, then atropine may modify the above gmfERG responses to retinal defocus.…”
mentioning
confidence: 99%
“…Recent data from Wolsley et al (2008), Ho et al (2012) and Chin et al (2015) confirms the dominant role of retina in the regulation of ocular growth. By using multifocal electroretinogram (mfERG) in humans, these authors have demonstrated dynamic changes in the peripheral retinal activity.…”
Section: The Autonomic Control Of Choroidal Thickness Changesmentioning
confidence: 82%